2014
DOI: 10.1002/nbm.3246
|View full text |Cite
|
Sign up to set email alerts
|

ZTE imaging with long‐T2 suppression

Abstract: Three-dimensional radial zero echo time (ZTE) imaging enables efficient direct MRI of tissues with rapid transverse relaxation. Yet, the feature of capturing signals with a wide range of T2 and T2 * values is accompanied by a lack of contrast between the corresponding tissues. In particular, the targeted short-T2 tissues may not be easily identified, and various approaches have been proposed to generate T2 contrast by reducing the long-T2 signal of water and/or fat. The aim of this work was to provide efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…IR-ZTE, therefore, cannot be directly compared to an optimized IR-UTE protocol, where the duration of the excitation pulse is more flexible, and the flip angle can be increased to the optimal 90°. This problem could be mitigated on our 3T clinical scanner by applying multiple readouts per inversion in an IR-rZTE-PETRA sequence (Li et al, 2016), and has also been reported on a small-bore imager (Weiger et al, 2015), but this sequence enhancement could not be implemented on the 9.4T system used in this study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…IR-ZTE, therefore, cannot be directly compared to an optimized IR-UTE protocol, where the duration of the excitation pulse is more flexible, and the flip angle can be increased to the optimal 90°. This problem could be mitigated on our 3T clinical scanner by applying multiple readouts per inversion in an IR-rZTE-PETRA sequence (Li et al, 2016), and has also been reported on a small-bore imager (Weiger et al, 2015), but this sequence enhancement could not be implemented on the 9.4T system used in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Some of these limitations in ZTE can be alleviated with a custom-designed multiple-readout pulse sequence as described in Section 2.2 above and references (Li et al, 2016) and (Weiger et al, 2015). No such pulse sequence was available for the experiments conducted on the 9.4T micro-imaging system.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, they possess extremely short relaxation times (T2* ,400 µsec), and conventional MR imaging modalities with an approximate echo time (TE) on the order of a few milliseconds (5-7 msec) are not capable of enabling any considerable information to be acquired from these water molecules. To obviate this limitation, solidstate MR imaging has been introduced, employing short, ultrashort, and, most recently, zero TEs, and is acknowledged to be a prevalent tool for imaging short T2* components (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…Further ZTE imaging optimizations, which consisted of short amplitude-and frequency-modulated pulses for high bandwidth RF excitation, and long T 2 suppression, led to a significant improvement of this technique for clinical use [40,41].…”
Section: Basic Principle Of Zero Echo Time Imagingmentioning
confidence: 99%